Desenvolvimento de blendas poliméricas PVC/NBR através de processamento reativo e vulcanização dinâmica in situ - Passador, Fabio Roberto (2008)
Dynamic vulcanization is a process of vulcanization of an elastomer during melt mixing with a thermoplastic which results in a material with better chemical and mechanical properties at high temperature. The PVC/NBR blends were obtained by reactive processing and in situ dynamic curing. The crosslinking of PVC/NBR blends was accomplished using sulphur (S)/tetramethylthiuram disulphide (TMTD) and mercaptobenzothiazyl disulphide (MBTS) curative system during the reactive processing. The blends of PVC/NBR at the ratio of 90/10; 80/20 and 70/30 wt% were melt mixed using an internal mixer at 160°C and rotor speed of 60rpm. The degrees of crosslinking of the blends obtained by the reactive process were analyzed through Fourier Transform InfraRed (FT-IR), swelling and degree of cure. Higher crosslink densities were obtained the systems with higher amount of elastomer. The mechanical properties evaluated by tensile properties, tear strength, hardness and compression set showed that the dynamic vulcanized blends have a better performance compared to the similar conventional ones. It was observed an increase of 92% in the tensile stress to the dynamic vulcanized blend PVC/NBR (70/30) with partitioning agent of PVC and an increase of 205% in the Young´s modulus to the dynamic vulcanized blend PVC/NBR (90/10) with partitioning agent of CaCO3. The morphology of the blends examined by scanning electron microscopy evidenced the crosslinking formation only in the elastomeric phase. The vulcanized rubber particles are responsible by the increase of stiffness and consequently displayed better mechanical properties.